Karakterisasi Sabut Siwalan (Borassus flabellifer) dan Kulit Pisang Raja (Musa paradisiaca var. Raja) dalam Proses Produksi Pembuatan Bioetanol - Fariha, Chandra Nur; Setiawan, Adhi; Ramadani, Tarikh Azis (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2020)
Palmera palm fiber (Borassus flabellifer) and banana peels (Musa paradisiaca var. Raja) are agricultural wastes that have high cellulose content. Utilization of Palmera palm fiber waste and banana peels as animal feed or organic waste. This waste can be used as raw material for making bioethanol which has a better selling point. This study aims to determine the characteristics of Palmera palm fiber and banana peels in the process of making bioethanol. The process of making bioethanol is consists of a fermentation process and batch distillation process. SEM results there is a morphological change from Palmera palm fiber (Borassus flabellifer) and banana peel (Musa paradisiaca var. Raja) before the delignification process and after the delignification process. Analysis using FTIR proved that the palmera palm fiber and banana peel before delignification contained O-H, C-O functional groups. and C-H so of these raw materials have the potential to produce ethanol. Ethanol content was measured using Gas Chromatography (GC) and an ethanol content of 1.011% was obtained.